Using the ensembl genome server to browse genomic sequence data - Fernández-Suárez, Xosé M; Schuster, Michael K (Current protocols in bioinformatics, 2010)
The Ensembl project provides a comprehensive source of automatic annotation of the human genome sequence, as well as other species of biomedical interest, with confirmed gene predictions that have been integrated with external data sources. This unit describes how to use the Ensembl genome browser (http://www.ensembl.org/), the public interface of the project. It describes how to find a gene or protein of interest, how to get additional information and external links, and how to use the comparative genomic data. Curr. Protoc. Bioinform. 30:1.15.1-1.15.48. (c) 2010 by John Wiley & Sons, Inc.